2023
DOI: 10.3390/ma16041407
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Intra-Oral Repair Systems for Veneered Zirconia and Zirconia Only

Abstract: The aim of this study was to compare bond strength resin composites to porcelain laminate veneers in the indirect repair method to composite resins used in the direct repair method for cases of porcelain veneer fracture of zirconia-based fixed dental prostheses. In the study, the groups were formed with different percentages of areas to be repaired to mimic porcelain fractures in the mouth. The experimental group of veneered zirconia were as follows: Group A = 100% Zr surface; Group B = 70% Zr, 30% porcelain s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…It has been reported that materials with silica-rich surfaces exhibit enhanced adhesion properties between the hydroxyl group on the silica surface and a silane coupling agent [46]. TSC or 'silicatization' treatment has been shown to increase µTBS due to the creation of both micromechanical and chemical modifications on the zirconia surface [47,48]. Further studies have reported that chemical conditioning (siloxane network) is more important than micromechanical modifications during resinceramic cementation [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that materials with silica-rich surfaces exhibit enhanced adhesion properties between the hydroxyl group on the silica surface and a silane coupling agent [46]. TSC or 'silicatization' treatment has been shown to increase µTBS due to the creation of both micromechanical and chemical modifications on the zirconia surface [47,48]. Further studies have reported that chemical conditioning (siloxane network) is more important than micromechanical modifications during resinceramic cementation [49,50].…”
Section: Discussionmentioning
confidence: 99%